Parenting Strategies and Adaptation among Muslim Families in the Prostitution-Affected Area of Samas Beach, Yogyakarta - Nugroho, Aji Setyo; A’isah, Anita (Jurnal Sosiologi Agama Indonesia (JSAI), 2025)
This study examines how Muslim families manage parenting in the prostitution-affected area of Samas Beach, Yogyakarta, where social and economic risks shape everyday life. Using a qualitative case study design, the research draws on in-depth interviews and participant observation with four families living in this unique context. The results reveal a spectrum of parenting strategies, from structured routines and active communication to more permissive patterns influenced by limited resources and parental absence. Parental backgrounds, especially experiences with past risk and hardship, often led parents to become more protective and intentional in raising their children. Economic pressures and irregular work schedules contributed to increased reliance on older siblings and less consistent daily supervision. Religious knowledge and community involvement sometimes supported families in guiding their children’s behavior, but could also present challenges when routines were disrupted. The findings highlight that parenting in a prostitution-affected environment requires ongoing adaptation and negotiation. These insights point to the importance of context-sensitive support systems for strengthening resilience among children and parents living in similar high-risk communities.